Data science for librarians - Du, Yunfei 1970-; Khan, Hammad Rauf (Santa Barbara, California Denver, Colorado Libraries Unlimited, an imprint of ABC-CLIO, 2020)
"This unique textbook intersects traditional library science with data science principles that readers will find useful in implementing or improving data services within their libraries"--Provided by publisher.
More data, more problems -- A new strand of librarianship -- Data creation and collection -- Data for the academic librarian -- Research data services and the library ecosystem -- Data sources -- Data curation (archiving/preservation) -- Data storage, management, and retrieval -- Data analysis and visualization -- Data ethics and policies -- Data for public libraries and special libraries -- Conclusion: library, information, and data science.
Includes bibliographical references and index.
Keywords: Database management in libraries; Data curation in libraries; Data services librarians; Research -- Data processing -- Management; Big data